VD_FINDINFO Arrêt / 2019 / 250 vom 29. Mai 2019 - VD Tribunal cantonal (2019)
FORMATION PROFESSIONNELLE, RENTE D'INVALIDITÉ, REVENU SANS INVALIDITÉ | 28 al. 2 LAI, 28a al. 1 LAI, 16 LPGA, 26 al. 2 RAI